Diagnosing Alzheimer’s Disease Based on Multiclass MRI Scans using Transfer Learning Techniques - Prakash, Deekshitha; Madusanka, Nuwan; Bhattacharjee, Subrata; Kim, Cho-Hee; Park, Hyeon-Gyun; Choi, Heung-Kook (Current Medical Imaging, 2021)
Aims: To prevent Alzheimer’s disease (AD) from progressing to dementia, early prediction and classification of AD are important and they play a crucial role in medical image analysis. Background: In this study, we employed a transfer learning technique to classify magnetic resonance (MR) images using a pre-trained convolutional neural network (CNN). Objective: To address the early diagnosis of AD, we employed a computer-assisted technique, specifically the deep learning (DL) model, to detect AD. Methods: In particular, we classified Alzheimer’s disease (AD), mild cognitive impairment (MCI), and normal control (NC) subjects using whole slide two-dimensional (2D) images. To illustrate this approach, we made use of state-of-the-art CNN base models, i.e., the residual networks Res- Net-101, ResNet-50, and ResNet-18, and compared their effectiveness in identifying AD. To evaluate this approach, an AD Neuroimaging Initiative (ADNI) dataset was utilized. We also showed uniqueness by using MR images selected only from the central slice containing left and right hippocampus regions to evaluate the models. Results: All three models used randomly split data in the ratio of 70:30 for training and testing. Among the three, ResNet-101 showed 98.37% accuracy, better than the other two ResNet models, and performed well in multiclass classification. The promising results emphasize the benefit of using transfer learning, specifically when the dataset is low. Conclusion: From this study, we know that transfer learning helps to overcome DL problems mainly when the data available is insufficient to train a model from scratch. This approach is highly advantageous in medical image analysis to diagnose diseases like AD.
Keywords: residual networks